Lighting-up breast cancer cells by a near-infrared fluorescent probe based on KIAA1363 enzyme-targeting. Issue 35 (19th April 2017) - Fan, Jiangli; Guo, Shigang; Wang, Suzhen; Kang, Yao; Yao, Qichao; Wang, Jia; Gao, Xue; Wang, Hongjiang; Du, Jianjun; Peng, Xiaojun
Abstract : NB-AX, the first NIR KIAA1363-targeting fluorescent probe, could be used for the ultrafast lighting up of breast cancer cells and detection of tissues and tumors in vivo . Abstract : The first NIR KIAA1363-targeting probe, NB-AX, specifically and instantly featured an "off–on" switch upon gradual addition of KIAA1363 over all kinds of other biomolecules, and its detection limit was initially calculated to be 0.58 μg mL −1 (3 δ / k ). The probe was also able to be used in ultrafast distinguishing of breast cancer cells from normal cells in fluorescence imaging and applied in tissue imaging and tumor imaging in vivo .